Towards the co‐ordination of terrestrial ecosystem protocols across European research infrastructures. Issue 11 (23rd April 2017) - Firbank, Les G.; Bertora, Chiara; Blankman, David; Delle Vedove, Gemini; Frenzel, Mark; Grignani, Carlo; Groner, Elli; Kertész, Miklós; Krab, Eveline J.; Matteucci, Giorgio; Menta, Christina; Mueller, Carsten W.; et al.
Abstract: The study of ecosystem processes over multiple scales of space and time is often best achieved using comparable data from multiple sites. Yet, long‐term ecological observatories have often developed their own data collection protocols. Here, we address this problem by proposing a set of ecological protocols suitable for widespread adoption by the ecological community. Scientists from the European ecological research community prioritized terrestrial ecosystem parameters that could benefit from a more consistent approach to data collection within the resources available at most long‐term ecological observatories. Parameters for which standard methods are in widespread use, or for which methods are evolving rapidly, were not selected. Protocols were developed by domain experts, building on existing methods where possible, and refined through a process of field testing and training. They address above‐ground plant biomass; decomposition; land use and management; leaf area index; soil mesofaunal diversity; soil C and N stocks, and greenhouse gas emissions from soils. These complement existing methods to provide a complete assessment of ecological integrity. These protocols offer integrated approaches to ecological data collection that are low cost and are starting to be used across the European Long Term Ecological Research community. Abstract : Here, a set of protocols is presented that measure major ecosystem stocks and processes, suitable for use across experiments and observatories. The protocols have been selected by the scientific community to support the integrated analysis of ecological data.